Breast Reconstruction After Mastectomy for Cancer: our Personal View - García Capurro, Rafael; Bermúdez, Jorge; Rocangliolo, Aldo; Fossati, Guillermo (Cirugía del Uruguay, 1981)
Breast cancer treatment is oncologicall'y achieved by modified radical mastectomy, with or without adjutant therapy.